A Lightweight Web Push Notification Framework for Educational Information SystemsSupporting Digital Transformation Through RealTime Web NotificationTechnology - Luqman Hakim (Universitas Bakti Indonesia, 2026)
This study presents the design and implementation of a lightweight Web Push Notification Framework for educational information systems using PHP Native, JavaScript, Service Worker, Web Push API [1], VAPID authentication, and MySQL. The proposed framework consists of four core modules: Service Worker [2], Push Subscription, Subscription Management, and Notification Delivery, enabling secure browser registration and automatic real-time notification delivery whenever new content is published. Experimental results confirm that the framework successfully performs browser registration, subscription storage, notification delivery, and content redirection across modern web browsers. The proposed framework provides a secure, scalable, and easily integrated solution for PHP-based web applications while establishing a foundation for future intelligent notification services.